ИЗУЧЕНИЕ МИКРООРГАНИЗМОВ ФАРША ИЗ ОСЕТРОВЫХ РЫБ (Experimental biology, 2017)
In this work the lactic flora of fish products, including fish mince prepared from sturgeon.
Keywords: lactic flora; fish products